A Pd–Cu2O nanocomposite as an effective synergistic catalyst for selective semi-hydrogenation of the terminal alkynes only. Issue 18 (8th February 2016) - Yang, Shuliang; Cao, Changyan; Peng, Li; Zhang, Jianling; Han, Buxing; Song, Weiguo
Abstract : A new type lead-free Pd–Cu2 O nanocomposite catalyst shows "double" selectivities for hydrogenation of alkynes: only terminal alkynes hydrogenated and only alkenes produced, i.e. no internal alkyne is hydrogenated. Abstract : A new type lead-free catalyst of a Pd–Cu2 O nanocomposite was developed for highly selective semi-hydrogenation of alkynes. With unprecedented selectivity for the semi-hydrogenation of terminal alkynes to alkenes, we show for the first time that the catalyst only hydrogenated the terminal alkynes, i.e. did not hydrogenate the internal alkynes.